Research methods in psychology : - Spatz, Chris (McGraw-Hill, 2008)
Emphasizing critical thinking and ethics, Spatz & Kardas’ Research Methods in Psychology presents a practical approach to investigating behavioral and mental processes. By understanding context, students are led to apply appropriate methods, collect data, and arrive at valid conclusions about subjects that relate to the world around them. Intended for a first undergraduate course, Research Methods in Psychology incorporates student-friendly features such as Chapter Reviews and Critical Thinking exercises, while providing all the background and tools necessary for students to conduct and report on their own research